Building an Effective Sweetpotato Community of Practice - International Potato Center (2014)
Building an effective Community of Practice (CoP) is essential if the goal of improving the lives of 10 million African households by 2020 is to be met. The Sweetpotato “Speedbreeders” built an effective CoP during SPHI Phase1, and during Phase 2, three additional CoPs will be supported.